2016
DOI: 10.3390/toxins8040095
|View full text |Cite
|
Sign up to set email alerts
|

ADAM10 Cell Surface Expression but Not Activity Is Critical for Staphylococcus aureus α-Hemolysin-Mediated Activation of the NLRP3 Inflammasome in Human Monocytes

Abstract: The Staphylococcus aureus toxin, α-hemolysin, is an important and well-studied virulence factor in staphylococcal infection. It is a soluble monomeric protein that, once secreted by the bacterium, forms a heptameric pore in the membrane of a broad range of host cell types. Hemolysin was recently discovered to bind and activate a disintegrin and metalloprotease 10 (ADAM10). In epithelial and endothelial cells, ADAM10 activation is required for the toxin’s activity against these cells. In host monocytic cells, α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 30 publications
1
25
1
1
Order By: Relevance
“…Notably, ADAM10 and ADAM17 contain a conserved active site sequence and, according to the primary structure of their catalytic sites, they belong to the same subgroup of ADAM proteinases [37,38]. That GI254023X inhibits binding of α-toxin, although mutation of the catalytic site of ADAM10 does not, might be due to non-canonical effects of the inhibitor [68], possibly involving factors that regulate ADAM10 expression, folding, traffic or surface presentation, as has been shown for Atg16L1 [69], eukaryotic initiation factor 2α (eIF2α)…”
Section: Discussionmentioning
confidence: 95%
“…Notably, ADAM10 and ADAM17 contain a conserved active site sequence and, according to the primary structure of their catalytic sites, they belong to the same subgroup of ADAM proteinases [37,38]. That GI254023X inhibits binding of α-toxin, although mutation of the catalytic site of ADAM10 does not, might be due to non-canonical effects of the inhibitor [68], possibly involving factors that regulate ADAM10 expression, folding, traffic or surface presentation, as has been shown for Atg16L1 [69], eukaryotic initiation factor 2α (eIF2α)…”
Section: Discussionmentioning
confidence: 95%
“…Binding of α-toxin to ADAM10 is necessary for α-toxin-induced cytotoxicity and the disruption of epithelial and endothelial barriers [8-11]. However, the molecular details of this process are unknown, in particular since a recent study demonstrated that the enzyme activity of ADAM10 is not required for at least some of the effects of α-toxin [12]. …”
Section: Introductionmentioning
confidence: 99%
“…The localization and decreased numbers of neutrophils likely resulted in less inflammation to facilitate more rapid wound healing. Although the mechanism by which neutralizing AT led to less neutrophil recruitment is not entirely clear, it could have been due to decreasing AT activation of the NLRP3/ASC inflammasome that processes pro-interleukin-1␤ (pro-IL-1␤) to active IL-1␤ (38)(39)(40)(41)(42), which is essential for mediating neutrophil recruitment to a site of S. aureus infection in the skin (41).…”
Section: Discussionmentioning
confidence: 99%